2008
DOI: 10.1063/1.2839597
|View full text |Cite
|
Sign up to set email alerts
|

Electron capture induced dissociation of nucleotide anions in water nanodroplets

Abstract: We have studied the outcome of collisions between the hydrated nucleotide anion adenosine 5'-monophosphate (AMP) and sodium. Electron capture leads to hydrogen loss as well as water evaporation regardless of the initial number m of water molecules attached to the parent ion (m< or =16). The yield of dianions with microsecond lifetimes increases strongly with m, which is explained from dielectric screening of the two charges by the water nanodroplet. For comparison, collision induced dissociation results in wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
1
31
1
Order By: Relevance
“…On the other hand, the subsequent fragmentation is certainly modified by the presence of solvent. The rapid coupling of vibrational energy into the solvent should occur on a time scale on the order of tens of picoseconds, making fragmentation energetically inaccessible [24]. In the gas phase, there is no such fast relaxation into the solvent, and fragmentation occurs on a multinanosecond [25] to microsecond [26] time scale.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the subsequent fragmentation is certainly modified by the presence of solvent. The rapid coupling of vibrational energy into the solvent should occur on a time scale on the order of tens of picoseconds, making fragmentation energetically inaccessible [24]. In the gas phase, there is no such fast relaxation into the solvent, and fragmentation occurs on a multinanosecond [25] to microsecond [26] time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Because the main component of living tissues is water, a first approach is to consider molecule-water clusters. [8,9] An alternative to experiments with such nanohydrated complexes is to study clusters of biomolecules. [10,11] Since DNA carries the genetic information, most of the studies have been focused on its constituents.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by the relative importance of the electron-capture process in comparison to the other dissociation channels as a function cluster size, i.e., the former being approximately constant with increasing cluster size [32]. We can mention that, in collision-induced fragmentation of water-solvated anions of adenosine 5 -monophosphate (AMP) with Na atoms, Liu et al [33,34] observed that the electron-capture process leads to a more important damaging effect when increasing the number of initially attached water molecules while they observed a protective behavior of the water molecules for collision-induced dissociation processes without electron transfer.…”
Section: Resultsmentioning
confidence: 99%